A flexible process-capability-qualified resubmission-allowed acceptance sampling scheme. (February 2015) - Wu, Chien-Wei; Shu, Ming-Hung; Nugroho, Alexander A.; Kurniati, Nani
Highlights: A flexible C pmk -qualified resubmission-allowed sampling scheme is developed. The OC curve of the proposed plan is derived using the exact sampling distribution. The efficiency of the proposed and existing plans are examined and compared. Tables of plan parameters are provided and an example is studied for illustration. Abstract: This paper introduces a new variables-acceptance-sampling scheme for resubmitted lots, based on process-capability-index ( C pmk ) sampling information. The scheme competently evaluates both the process yield and the potential process loss of the submitted lots. Vital criteria and decision rules, by which inspected lots are approved in the resubmitted sampling strategy, include required sample size for inspection, critical acceptance levels stipulated for quality standards, and risks to producers and consumers. To obtain these vital criteria, the operating function of the proposed sampling scheme is derived based on the exact sampling distribution of the C pmk estimator. In terms of the given rules and criteria, the resubmitted sampling plans provide greater insights than traditional single sampling plans. Finally, our proposed process-capability-qualified resubmission-allowed sampling strategy is evaluated on an industrial example.